2021
DOI: 10.26618/exposure.v10i1.4981
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Communicative Language Teaching to Increase the Students’ Motivation

Abstract: This research aimed to improve the students’ motivation by using Communicative Language Teaching (CLT) Method in teaching English at the Third Semester of Dental Nurse Department Poltekkes Kemenkes Makassar. The teaching material was English for Specific Purposes and the subjects of the research consisted of two classes, they were class A as a control class and class B as an experimental class. This research used quasi-experimental design with nonequivalent control group design.  The research indicated signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, Johnson and Johnson (1998) identify five core characteristics that underlie current applications of communicative methodology: appropriateness, message focus, psycholinguistic processes, risk taking and free practice. Research done in Indonesia by Basir et al (2021) showed that the use of CLT in teaching was improving English language learning motivation than the use of Grammar translation method. Similarly, a research done in Saudi Arabia by Sharma (2018) teaching methods that support motivation contribute to students' acquisition of communicative competence.…”
Section: Communicative Language Teaching Methodsmentioning
confidence: 99%
“…In addition, Johnson and Johnson (1998) identify five core characteristics that underlie current applications of communicative methodology: appropriateness, message focus, psycholinguistic processes, risk taking and free practice. Research done in Indonesia by Basir et al (2021) showed that the use of CLT in teaching was improving English language learning motivation than the use of Grammar translation method. Similarly, a research done in Saudi Arabia by Sharma (2018) teaching methods that support motivation contribute to students' acquisition of communicative competence.…”
Section: Communicative Language Teaching Methodsmentioning
confidence: 99%